1998
DOI: 10.1007/s004220050445
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory formation based on physiological characteristics of skeletal muscles

Abstract: Human arm trajectories in natural unrestricted reaching movements were studied. They have particular properties such that a hand path is a rather simple straight or curved line, and a tangential velocity profile of hand is bell-shaped. Also these properties are invariant, independent of movement duration and hand-held load. In this study, trajectory formation is investigated on the basis of physiological characteristics of skeletal muscles, and a criterion prescribed by a derivative of isometric muscle torque … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Several theories of motor control are based on or inspired by the idea that the CNS arrives at a set of muscle activation patterns for a given task by minimizing a cost function in which minimization of energy cost takes part (e.g., Alexander 1997;Cruse 1986;Engelbrecht 2001;Hatze and Buys 1977;Kashima and Isurugi 1998;Nelson 1983;Rasmussen et al 2001;Soechting et al 1995;Todorov 2004;Todorov and Jordan 2002;Torres and Zipser 2002). Such theories have been shown to predict kinematic features for movement tasks in the absence of external loads, like relatively straight hand paths and bell-shaped velocity profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Several theories of motor control are based on or inspired by the idea that the CNS arrives at a set of muscle activation patterns for a given task by minimizing a cost function in which minimization of energy cost takes part (e.g., Alexander 1997;Cruse 1986;Engelbrecht 2001;Hatze and Buys 1977;Kashima and Isurugi 1998;Nelson 1983;Rasmussen et al 2001;Soechting et al 1995;Todorov 2004;Todorov and Jordan 2002;Torres and Zipser 2002). Such theories have been shown to predict kinematic features for movement tasks in the absence of external loads, like relatively straight hand paths and bell-shaped velocity profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars have made great efforts to explain observed trajectories as solutions to optimization problems. Optimization criteria have been proposed including minimum jerk theory (Flash and Hogan, 1985), minimum travel cost theory (Rosenbaum et al, 1995), minimum isometric torque derivative (Kashima and Isurugi, 1998), and averaged specific power (Secco et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Humanlike body motions are necessary to implement humanlike behavior in an android. There have been several studies on the generation of humanlike motion, including studies on a model to generate human motion trajectories based on a neurocomputational approach (Flash & Hogan, 1985;Uno et al, 1989;Kawato, 1992;Schaal & Sternad, 2001), a study on the control of a manipulator based on a model of motion trajectories of a person's arm (Kashima & Isurugi, 1998), and studies on a computer graphics (CG) animated characters, which have shown that noise in the motion makes the character's motion more humanlike (Perlin, 1995;Bodenheimer et al, 1999). These studies successfully generated a humanlike motion.…”
Section: Introductionmentioning
confidence: 99%